Turismo minero en Yanacocha: Una alternativa de desarrollo para la región de Cajamarca-Perú: Mining tourism in Yanacocha. A development alternative for the Cajamarca-Peru region - Nugra Betancourth, Mónica Alexandra; Illescas Espinoza, Wilmer Henry; Cuadros García, Paquita Alejandra; Valdivia Ramos, Roman Arturo (Revista de Ciencias Sociales, 2021)
Peru has had a long mining tradition that has extended into the 21st century, being a source of foreign exchange generation that has contributed to maintaining the macroeconomic balance of the nation. The objective of this work was to analyze the possibility of mining tourism in the company Yanacocha S.A., as a development alternative for the Cajamarca region - Peru. The methodological aspects include a type of exploratory-descriptive study, using direct observation and forecasting formulas (future projections). The results show that the mining activity of this company, despite having high levels of productivity and income, has left few benefits to the region where it is located; being relevant the activation of a mining tourism project that articulates production and service provision, as a symbiosis capable of encouraging the development of the region, since not only would the elements of extractive activity in a real mine be shown, but also The benefits of Cajamarca would also be offered in terms of accommodation, gastronomy and people. It is concluded that these aspects must be worked on as part of the intangible heritage of a locality and can be used to generate economic resources.RESUMENABAS